Trunk muscle aerobic metabolism responses in endurance athletes, combat athletes and untrained men - Anthierens, A.; Olivier, N.; Thevenon, A.; Mucci, P. (International Journal of Sports Medicine, 2019)
This study investigated aerobic metabolism responses in trunk muscles during a prolonged trunk extension exercise in athletes and untrained young men. The aim was to analyze the adaptations induced by 2 types of sports: one involving intensive use of trunk muscles (i. e., judo), and one known to induce high aerobic capacity in the whole body (i. e., cycling). Eleven judokas, 10 cyclists and 9 healthy untrained young men performed trunk extension exercises on an isokinetic dynamometer. During the first session, muscle strength was assessed during maximal trunk extension. During a second session, a 5-min exercise was performed to investigate aerobic responses with regard to trunk muscles. The near infrared spectroscopy technique and a gas exchange analyzer were used continuously to evaluate mechanical efficiency, VO2 on-set kinetics, trunk muscle deoxygenation and blood volume. Judokas showed greater trunk strength and mechanical efficiency (p<0.05). Cyclists presented faster VO2 on-set kinetics (p<0.05) and greater muscle deoxygenation and blood volume compared to untrained men (p<0.001). These results suggest that practicing judo improves trunk extension efficiency whereas cycling accelerates aerobic pathways and enhances microvascular responses to trunk extension exercise. Sport practice improves aerobic metabolism responses in trunk extensor muscles differently, according to the training specificities.